Improving Basketball Free-Throw Accuracy Through the BEEF Method: An Experimental Study in School-Based Extracurricular Players - Hardi, Veny Juniarni; Malik, Rafly Zaenal; Rismayadi, Alen (STKIP Pasundan, 2025)
This study aims to determine the application of shooting exercises using the Beef method to the accuracy of free throws of basketball extracurricular students at Cimahi State Junior High School 5. This study uses the pre-test and post-test one-group experimental method. The research population is students who actively participate in basketball extracurricular extracurricular at Cimahi State Junior High School 5. Sampling uses purposive sampling techniques so that 10 students are obtained as samples that meet the specified criteria. The results showed a significant increase in the accuracy of free throws of basketball extracurricular students, indicated by the average difference before and after treatment (pre-test = 3.7 and post-test = 6.20) and t-test (t-count = -7,319; p = 0.000 <0.05). Thus, the application of shooting exercises using the BEEF method can increase the accuracy of free throws of basketball extracurricular students in Cimahi State Junior High School 5.